Development of Interactive E-LKPD Based on Project-Based Learning to Enhance Self-Learning and Student Differentiation - Syahfitri, Dina Yogi; Januarini, Fitri Rizki Erna Januarini Fitri; Harahap, Nursaima Harahap Nursaima; Kesuma, Rini Kesuma Rini (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This research focuses on the development of an Electronic Student Worksheet (E-LKPD) based on Project-Based Learning (PBL) for Indonesian language subjects, aiming to ensure that it is valid, effective, and practical in enhancing student learning outcomes. The study employs a Research and Development (RD) approach utilizing the 4-D model, which includes four stages: defining, designing, developing, and disseminating. The E-LKPD developed was subjected to validity, effectiveness, and practicality tests. The findings indicated that the E-LKPD on biodiversity materials achieved a validity score of 3.28 from a team of subject matter experts and design validators. Additionally, feedback from students and teachers showed that the practicality of the teaching materials was rated positively with an average score of 3,5. When assessing learning outcomes through the use of the E-LKPD based on PBL, students scored an average of 80.86, categorizing their performance as very high with a mastery percentage of 93%. Consequently, the E-LKPD based on PBL is deemed appropriate for use as it meets the criteria for validity, effectiveness, and practicality. The implications of this development suggest that the PBL-based E-LKPD can enhance the development model utilized to produce higher quality educational products that assist in the learning process.